Systemic risk of insurers around the globe - Bierth, Christopher; Irresberger, Felix; Weiß, Gregor N.F. (Journal of Banking & Finance, 2015)
We study the exposure and contribution of 253 international life and non-life insurers to systemic risk between 2000 and 2012. For our full sample period, we find systemic risk in the international insurance sector to be small. In contrast, the contribution of insurers to the fragility of the financial system peaked during the recent financial crisis. In our panel regressions, we find the interconnectedness of large insurers with the insurance sector to be a significant driver of the insurers’ exposure to systemic risk. In contrast, the contribution of insurers to systemic risk appears to be primarily driven by the insurers’ leverage.